Influence of plane wave cut-off on structural and electronic properties in Sn-BEA and Ti-BEA zeolite water molecule interaction - Kulkarni, Bhakti S.; Krishnamurty, Sailaja; Pal, Sourav (Chemical Physics Letters, 2010)
Periodic systems are best described by the pseudo-potential methods. However, the accuracy of its description depends on the cut-off of plane wave basis. This is much more critical in the case of weak interactions, where a clear understanding on the influence of plane wave cut-off on the structural and electronic properties is not readily available in the literature. In the present work, we have taken a metal substituted beta zeolite-H2O complex for understanding this objective. Our studies show that while a lower cut-off of 500 eV is sufficient for the convergence of the structural parameters, description of energy-dependent properties necessitates a high cut-off value. (C) 2009 Elsevier B.V. All rights reserved.

Influence of charge and ligand on the finite temperature behavior of gold clusters: a BOMD study on Au-6 cluster - Manzoor, Dar; Pal, Sourav; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2013)
Conformation and electronic charge on a gold cluster are known to determine its catalytic property. However, little is known on the finite temperature behavior of various gold cluster conformations. Much less is known on the role of charge or a ligand in stabilizing a conformation at finite temperatures. In this work, we have carried out relativistic density functional theory (DFT) based molecular dynamical simulations on neutral and charged Au-6 clusters with an aim of understanding the stability of ground state conformations as a function of charge on the cluster. Our simulations reveal that cationic and anionic Au-6 clusters undergo conformational transitions at 500 K where as neutral Au-6 cluster retains its ground state conformation up to a temperature of 1100 K. In order to look into the factors leading to the stabilization of neutral Au-6 cluster (or destabilization of cationic and anionic Au-6 clusters), structural and electronic properties are analyzed. Factors such as charge redistribution within the atoms and composition of molecular orbitals are seen to contribute towards stronger Au-Au bonds in Au-6(0) thereby stabilizing it considerably. Following the analysis, simulations are also extended to neutral, cationic, and anionic Au-6-COn (n = 1,2) complexes. In the case of CO chemisorbed Au-6 clusters, neutral and negatively charged ground state conformations are stable up to nearly 800 K, while the positively charged Au-6 ground state conformation collapses at room temperature. This work, in short demonstrates how charge or even a ligand can be used to moderate the physical properties of a gold cluster.

Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

An innovative light assisted production of acetic acid from CO2 and methanol: a first photocatalytic approach using a reusable cobalt(ii) molecular hybrid at atmospheric pressure - Saini, Sandhya; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Ray, Anjan; Jain, Suman L. (Green Chemistry, 2021)
Acetic acid is an important commodity chemical that is produced either by fermentation processes, or more commonly, through chemical routes such as methanol carbonylation with CO and H-2, acetaldehyde oxidation, or hydrocarbon oxidation. More recently, methanol hydrocarboxylation with CO2 and H-2 under thermal catalytic conditions has attracted interest. The synthesis of acetic acid from easily available CO2 is of great significance yet rarely reported. The present paper describes the first photocatalytic approach for the synthesis of acetic acid from methanol and CO2 under ambient reaction conditions without using molecular hydrogen. The maximum conversion of methanol achieved is 60% with a selectivity of 81% towards acetic acid using an octa-sulfur bound cobalt phthalocyanine (CoPc/S8) photocatalyst without an additional sacrificial electron donor. Product analysis, controlled experiments and DFT calculations suggest the formation of methylene carbene as a reactive intermediate. The developed methodology represents a potentially exciting approach for synthesizing acetic acid utilizing CO2 in a sustainable manner.

Insights into adsorption of various gases on extra-framework cations of zeolite: a dispersion corrected DFT study on zeolite cluster models with Li plus , Na plus and K plus ions - Devasia, George; Kumar, Ravi; Vaval, Nayana; Krishnamurty, Sailaja (Microporous and Mesoporous Materials, 2023)
Design of an economical and sustainable gas separation material is relevant in several industrial processes. Zeolites with tunable pore sizes are ideal molecular sieves of many gases. The adsorption centers of these molecular sieves are extra-framework Lewis acid centers. In this study, we attempt to delineate the electronic properties of such centers (Li+, Na+ and K+) and their sorption properties towards N2, O2, CO, CO2 and H2. Negative framework of zeolites are modeled using different cluster models that present distinct electronic environment and role of this environment on the Lewis acidity of the cation. The sorption property towards different gases is evaluated using dispersion corrected DFT studies. The results obtained are benchmarked for one of the studied model using CCSD calculations. The results indicate that while the local environment modulates the adsorption properties, the relative adsorption properties between different ions follow the same order irrespective of the type of negative framework modeled. This reveals that intrinsic atomic properties of the charge compensating cations drive the sorption properties of the zeolites. Adsorption energies compounded with the analysis of IR stretching frequencies of the adsorbed gases reveals that Li centers shows molecular adsorption (charge donation to the cationic centers) towards N2 as compared to O2 and towards CO2/CO as compared to H2, demonstrating the applicability of Li-Zeolites as ideal membranes for oxygen concentrators and syngas separation. These adsorption studies are ratified by the BOMD simulations at 300 K, where H2 and O2 desorbs while N2, CO and CO2 remains adsorbed to the cationic site.
Keywords: BOMD simulation; CO/CO2/H2 separation; Extra-framework cation; N2/O2 separation; zeolites

Investigation of the effect of zeolite supports and the role of W-species for one-pot catalytic conversion of cellulose to ethylene glycol: theoretical & experimental studies. - Sreekantan, Sreejith; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Marimuthu, Banu (Chemistry-An Asian Journal, 2023)
Endeavors were made to study the influence of various zeolite (HY, NaY, NaZSM-5 and HZSM-5) supports with (Al)-Ni-W metal combination catalysts for the ethylene glycol (EG) production, selectively from cellulose. From the experimental results ZSM-5 (NaZSM-5/73.3% & HZSM-5/67.7%) support is superior over HY & NaY support in selective EG production from cellulose. It was understood that W- species with oxygen vacancies (WO3-x, XPS analysis) plays an important role in producing the glycolaldehyde (GA) intermediate (via C-C cleavages), which on hydrogenation over Ni- sites selectively produce EG. Further, the studies based on the Density Functional Theory (DFT) were conducted to substantiate the involvement of the WO3-x species in the reaction. The adsorption energies and structural changes establish that the C-2-C-3 bond of the glucose elongates and thereby activates on adsorbing to WO3-x sites supporting the formation of GA. Activation of GA on Ni- sites is distinguished by an increase of 0.1 angstrom in C=O bond length, which facilitates the hydrogenation of C=O resulting in EG. The reaction pathway is explained through an analysis of CDD and DOS.
Keywords: Cellulose hydrogenolysis; DFT studies; ethylene glycol; zeolites

Iron-catalyzed regioselective C-H alkylation of indoles: an additive-free approach in renewable solvent - Pradhan, Chandini; Jagtap, Rahul A.; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Green Chemistry, 2023)
Alkylated indoles are important motifs in various biologically active molecules and drug candidates. Herein, we report a mild and efficient iron-catalyzed protocol for synthesizing alkylated indoles via C-H bond alkylation of indoles with unactivated alkenes, demonstrating a high level of regioselectivity. The reaction occurs under additive-free, solvent-free (or trace green solvent, 2-MeTHF) and less energy-intensive conditions using a sustainable metal catalyst and provides easy access to privileged alkylated indoles with anti-Markovnikov selectivity. Alkylation is compatible with important functionalities, such as fluoro, chloro, trifluoromethyl, alkenyl, ether, thioether, silyl, and siloxane, including heteroaryl, pyridinyl, carbazolyl, and indolyl moieties (45 examples, up to 96% yield). The developed protocol is very simple, straightforward, and fully accords with the principles of green chemistry. A detailed mechanistic investigation manifests the facile indole's C-H activation at the Fe(0) center, reversible 1,2-insertion of the alkene into the Fe-H bond of a metallacycle, and a turnover-limiting reductive elimination. Alkylated indoles are important motifs in various biologically active molecules and drug candidates.
Keywords: Aromatic Ketones; Green; organic synthesis

Indazole-5-amine (AIA) as competing corrosion coating to Benzotriazole (BTAH) at the interface of Cu: A DFT and BOMD case study - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Tiwari, Shivani; Shah, Vaishali; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2024)
This study compares three organic compounds-benzotriazole (BTAH), imidazole (IM), and indazole-5-amine (AIA)-as corrosion inhibitors for copper substrates. Using Density Functional Theory (DFT) and Born-Oppenheimer Molecular Dynamics (BOMD) calculations, it identifies AIA as a promising and cost-effective alternative to the toxic BTAH. The adsorption strength on Cu(1 0 0) surfaces is ranked AIA>BTAH>IM for both neutral and deprotonated forms. These findings are supported by electronic parameter studies, including Bader charge analysis, density of states (DOS), charge density differences (CDD), and frontier molecular orbital analysis. AIA shows the best adsorption in a parallel orientation at the top site. Packing studies reveal that hydrogen bonding stabilizes the interaction energies within self-assembled AIA aggregates. Organometallic complexation studies reveal that deprotonated BTAH exhibits higher interaction energy with a single Cu atom compared to AIA when bonded through the carbon end, consistent with the findings from BOMD studies. However, on periodic Cu surfaces, AIA outperforms BTAH molecules as seen from adsorption energies. This investigation highlights AIA's potential as a superior and more economical corrosion inhibitor for copper.
Keywords: Adsorption; Born-Oppenheimer molecular dynamics; Corrosion inhibition; Density functional theory; Indazole derivatives

Investigation of cathinone analogs targeting human dopamine transporter using molecular modeling - Shivankar, Bhavana R.; Bhandare, Vishwambhar Vishnu; Joshi, Krati; Patil. Vishal S.; Dhotare, Priyanka Shrikant; Sonawane, Kailas Dasharath; Krishnamurty, Sailaja (Journal of Biomolecular Structure & Dynamics, 2024)
In a step towards understanding the structure–property relationship among Synthetic Cathinones (SCs), a combined methodology based on Density Functional Theory (DFT), Administration, Distribution, Metabolism, Excretion, and Toxicity (ADMET) predictions, docking and molecular dynamics simulations have been applied to correlate physicochemical descriptors of various SCs to their biological activity. The results from DFT and molecular docking studies correlate well with each other explaining the biological activity trends of the studied SCs. Quantum mechanical descriptors viz. polarizability, electron affinity, ionization potential, chemical hardness, electronegativity, molecular electrostatic potential, and ion interaction studies unravel the distinguishingly reactive nature of Group D (pyrrolidine substituted) and Group E (methylenedioxy and pyrrolidine substituted) compounds. According to ADMET analysis, Group D and Group E molecules have a higher probability of permeating through the blood–brain barrier. Molecular docking results indicate that Phe76, Ala77, Asp79, Val152, Tyr156, Phe320, and Phe326 constitute the binding pocket residues of hDAT in which the most active ligands MDPV, MDPBP, and MDPPP are bound. Finally, to validate the derived quantum chemical descriptors and docking results, Molecular Dynamics (MD) simulations are performed with homology-modelled hDAT (human dopamine transporter). The MD simulation results revealed that the majority of SCs remain stable within the hDAT protein’s active sites via non-bonded interactions after 100 ns long simulations. The findings from DFT, ADMET analysis, molecular docking, and molecular dynamics simulation studies complement each other suggesting that pyrrolidine-substituted SCs (Group D and E), specifically, MPBP and PVN are proven potent SCs along with MDPV, validating various experimental observations.

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter

In silico designing of electrocatalysts for hydrogen evolution reaction: a focus on titanium metal-based diboride monolayers - Shivankar, Bhavana R.; Verma, Tushar Singh; Krishnamurty, Sailaja (International Journal of Hydrogen Energy, 2025)
Enhancing the efficiency of Hydrogen Evolution Reaction (HER) using chemically modified electrocatalytic titanium diboride surfaces with transition metal-based Single Atom Catalysts (SACs) is illustrated using Density Functional Theory (DFT) based methods employing solvent effects. With higher surface concentrations of nonmetal boron rather than titanium metal, these highly conductive, extremely hard, chemically, and thermally stable electrocatalysts are more cost-effective and superior to their MBene analogs. A systematic analysis of these transition metal-based SACs from the 3d, 4d, and 5d groups embedded in TiB2 monolayer for its HER activity reveals the reduction in limiting potential. As the most effective SAC for improved HER, Zn@TiB2 SAC has a limiting potential of 0.08 eV in acidic and 0.21 eV in alkaline media. The higher exchange current density of Zn@TiB2 (5.74 x 10-5 A cm-2), which exceeds most previously reported electrocatalysts, indicates exceptional HER performance. This work shows that transition metal boride electrocatalysts are economically viable for HER and pave a path for experimentalists.
Keywords: AIMD; D -band center; DFT; HER; SAC

Integrated flue gas CO2 capture and conversion to formate: a sustainable approach - Kumar, Rohit; Majumder, Supriyo; Singh, Chadrodai Pratap; Samanta, Chanchal; Newalkar, Bharat L.; Krishnamurty, Sailaja; Das, Raj Kumar (ChemSusChem, 2025)
Industrial CO2 emissions, characterized by dilute streams and impurity complexity, demand energy-efficient mitigation strategies beyond conventional capture technologies. Here, an integrated CO2 capture and conversion (ICCC) system is reported employing a heterogenized iridium catalyst-hydroxyquinoline-ligated Cp*Ir-Cl immobilized on amine-functionalized silica-that directly converts CO2 from synthetic flue gas containing SOx, NOx, and O2 to formate with 100% selectivity. The catalyst delivers remarkable activity, achieving turnover numbers up to 10,286 within 16 h. Density functional theory reveals that its square pyramidal geometry, induced by the hydroxyquinoline ligand, enhances Ir-N(ring) bond strength and electronic delocalization, thereby improving hydration energy, structural robustness, and catalytic efficiency. Importantly, the catalyst system demonstrates excellent durability, maintaining full activity over five regeneration cycles. Hydrogenation in a 1 M DABCO medium, followed by thermal decomposition of the amine-formate adduct at 150 degrees C, enables efficient lean amine regeneration, allowing subsequent flue gas capture and formate production without performance loss. This closed-loop strategy delivers a sustainable, contaminant-tolerant, and recyclable CO2-to-formate platform with strong promise for scalable industrial deployment.
Keywords: CO2 capture; flue gases; integrated capture and conversions; net zero future; Recycle